High-Performance Gate-All-Around Field Effect Transistors Based on Orderly Arrays of Catalytic Si Nanowire Channels - Liao, Wei; Qian, Wentao; An, Junyang; Liang, Lei; Hu, Zhiyan; Wang, Junzhuan; Yu, Linwei (Nano-Micro Letters, 2025)
Gate-all-around field-effect transistors (GAA-FETs) represent the leading-edge channel architecture for constructing state-of-the-art high-performance FETs. Despite the advantages offered by the GAA configuration, its application to catalytic silicon nanowire (SiNW) channels, known for facile low-temperature fabrication and high yield, has faced challenges primarily due to issues with precise positioning and alignment. In exploring this promising avenue, we employed an in-plane solid–liquid-solid (IPSLS) growth technique to batch-fabricate orderly arrays of ultrathin SiNWs, with diameters of DNW = 22.4 ± 2.4 nm and interwire spacing of 90 nm. An in situ channel-releasing technique has been developed to well preserve the geometry integrity of suspended SiNW arrays. By optimizing the source/drain contacts, high-performance GAA-FET devices have been successfully fabricated, based on these catalytic SiNW channels for the first time, yielding a high on/off current ratio of 107 and a steep subthreshold swing of 66 mV dec−1, closing the performance gap between the catalytic SiNW-FETs and state-of-the-art GAA-FETs fabricated by using advanced top-down EBL and EUV lithography. These results indicate that catalytic IPSLS SiNWs can also serve as the ideal 1D channels for scalable fabrication of high-performance GAA-FETs, well suited for monolithic 3D integrations. Highlights: 1 A high-density array of orderly silicon nanowires (SiNWs) was grown in precise locations, with diameter of DNW = 22.4 ± 2.4 nm and interwire spacing of 90 nm. 2 A special suspension-contact protocol has been developed to reliably suspend the in-plane solid-liquid-solid SiNWs to serve as ultrathin quasi-1D channels for gate-all-around field-effect transistors (GAA-FETs). 3 By optimizing the source/drain metal contacts, high-performance catalytical GAA-FETs have been successfully demonstrated, achieving a high on/off current ratio of 107 and a steep subthreshold swing of 66 mV dec-1.